Two new ricinuleid species from Ecuador and Colombia belonging to the peckorum species-group of Cryptocellus Westwood (Arachnida, Ricinulei) - Botero-Trujillo, Ricardo; Flórez, Eduardo D. (Zootaxa, 2017)
Two new ricinuleid species, Cryptocellus chiruisla sp. nov., from Orellana (Ecuador), and Cryptocellus guaviarensis sp. nov., from Guaviare (Colombia), are herein described. Both species, here assigned to the peckorum species-group, share a series of male features for which they most closely resemble each other: a flat, triangle-like region on the anterior section of cucullus; a pronounced ventral “notch” on leg I tibia; and a lateral compression on leg I metatarsus. These new taxa raise to three and nine the number of ricinuleid species known from Ecuador and Colombia, respectively. Cryptocellus Westwood, 1874 now consists of 42 species, six of which belong to the peckorum group.